2016
DOI: 10.18410/jebmh/2016/489
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Lipid Profile in Prediabetes

Abstract: BACKGROUND Lipid abnormalities are common in diabetes mellitus and play an important role in acceleration of atherosclerosis leading to increased cardiovascular diseases. Due to increasing burden of diabetes, it is becoming important to identify dyslipidaemia in high-risk state for diabetes especially prediabetes so that early intervention can reduce cardiovascular risk. AIM To study lipid profile in prediabetes individuals. METHODS This study was a cross-sectional case control study which included 107 prediab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Evaluation of the serum lipid parameters showed an elevation of total cholesterol, LDL cholesterol and serum triglycerides above normal limits even in the control group which comprised of obese normo-glycemic individuals. This lends weightage to studies carried out by Franssen R, et al [4] and Wang H, et al [5] . Who studied the impact of obesity on triglycerides and concluded that there is a positive correlation between these entities.…”
Section: Discussionsupporting
confidence: 61%
“…Evaluation of the serum lipid parameters showed an elevation of total cholesterol, LDL cholesterol and serum triglycerides above normal limits even in the control group which comprised of obese normo-glycemic individuals. This lends weightage to studies carried out by Franssen R, et al [4] and Wang H, et al [5] . Who studied the impact of obesity on triglycerides and concluded that there is a positive correlation between these entities.…”
Section: Discussionsupporting
confidence: 61%
“…15 About 5-10% of pre-diabetic patient become diabetic annually and nearly 70 % of pre-diabetics eventually develop diabetes mellitus if not treated in early stage. 16 Macro and micro vascular complications can start in IGT and early detection and treatment of dyslipidemia in IGT will decrease the risk of cardiovascular diseases (CVD). 15 Fasting blood glucose (FBG), post prandial blood glucose (PPBG) and glycated hemoglobin (HbA1c) are most widely used as glycemic control markers.…”
Section: Introductionmentioning
confidence: 99%
“…But very few studies are done in IGT in this regard. 15,16 . Thus, the aim of this study was to find comparison and correlation between FBG, PPBG andHbA1cwith lipid profile in T2DM patients and IGT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, people's job plays a fundamental role in their daily physical activity, in which it has been reported that office employees spend 66 to 82% of their time inactive and almost 75% in seated positions, which lead to increased risk of obesity and its related diseases, such as diabetes, non-alcoholic fatty liver disease, and cardiovascular disease [4][5][6][7].Also, Corresponding author: Mohsen Parvani, Master student of physical education and sport science faculty of Allameh Tabataba'I University, research fields: Exercise physiology.…”
Section: Introduction mentioning
confidence: 99%